Green Retail Model Berbasis Jejak Karbon di Kabupaten Sleman D.I.YOGYAKARTA - Feris Firdaus (Jurnal Green Growth dan Manajemen Lingkungan, 2021)
The increase in the number of retail on urban roads in Sleman D.I. Yogyakarta Regency has been very fast in recent years. The large number of retail visitors who use motorized vehicles and park in the area causes the emission of exhaust gas (CO2) to increase coupled with air conditioning exhaust gas from retail. In fact, many street vendors who cook food in the area use LPG gas so that there is an abundance of CO2 gas in the air in the retail area. On the other hand, it is very rare to find vegetation (trees) as an absorber of CO2 gas in the air in the retail area. Therefore, it is necessary to calculate the carbon footprint generated from activities in the retail area so that it can be seen how many trees need to be planted to absorb CO2 gas. Based on the results of carbon footprint analysis, it can be concluded that each retailer contributes to carbon emissions in the air (CO2) at different levels so that the number of trees that need to be planted is also different. The recommended tree should have a strategic function as an absorber of CO2 emissions in addition to other aesthetic and strategic functions. The recommended trees can be planted in motorized vehicle parking areas and street vendors that cook food.